Efficiency of influence of trainings loadings directed on «undercutting backward» qualities of young bicyclists 13–16 years - Воропай [Voropay S.], Сергій Миколайович (Slobozhanskyi Herald of Science and Sport, 2012)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> Efficiency of development of the special physical preparedness of young bicyclists is considered 13–16 years at the orientation of the trainings affecting on «undercutting of backward» qualities. In research 15 young bicyclists took part 13–16 years. The program of researches was made taking into account character of motive activity. Primary orientation of the training loading on «undercutting of backward» qualities. A pedagogical experiment was conducted the method of «cross study». Certainly efficiency of development of the special physical preparedness of young bicyclists 13–16 years at the orientation of the trainings affecting on «undercutting of backward» qualities. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->